Stability and Hopf Bifurcation Analysis of a Vector-Borne Disease with Time Delay - Yuanyuan Chen; Ya-Qing Bi (Journal of Applied Mathematics)
A delay-differential modelling of vector-borne is investigated. Its dynamics are studied in terms of local analysis and Hopf bifurcation theory, and its linear stability and Hopf bifurcation are demonstrated by studying the characteristic equation. The stability and direction of Hopf bifurcation are determined by applying the normal form theory and the center manifold argument.